An Examination of Gene Expression (Acc Oxidase and Receptor-Like Protein Kinases) in Somatic Embryogenesis of Oil Palm (Elaeis Guineensis) - See, Pao Theen (2002)
In plants, complete embryos can develop not only from the zygote, but also from somatic cells. This biological process is known as 'somatic embryogenesis'. Plant regeneration via somatic embryogenesis has provided the means for the application of biotechnology techniques such as clonal propagation, genetic transformation and cryopreservation. The significant potential of this in vitro propagation has resulted in a spate of exploration in a wide range of plants particularly commodity crops.In Malaysia, somatic embryogenesis of oil palm (Elaeis guineensis Jacq.) has generated a great deal of research interest. Although the totipotency of somatic cells has been documented in oil palm (Schwendiman et al., 1990; Duval et al., 1995; Wong et al., 1999), the mechanism of how the somatic cells undergo the change in fate to become embryogenic remains largely unknown. The understanding of this fundamental process is vital for the development of an economically viable propagation system. Hence, this study was conducted to explore the molecular events of oil palm somatic embryogenesis to enable isolation of developmental stage-specific markers that will greatly facilitate the improvement of the in vitro system. Two different approaches were carried out to identify these genes. In the first approach, specific genes from the multi gene family of protein kinases were isolated and their expression profiles were examined during oil palm somatic embryogenesis. Three receptor-like protein kinases (RLKs) designated as D4.5, E8.1.1 and F3.1 were characterised in this study. Expression studies and sequence analysis have revealed plausible roles of D4.5 and F3.1 as components of the plant growth regulator induced signalling pathway, meanwhile E8.l.1 most probably plays a role in mediating disease-resistance. The second approach was to use the strategy of suppression subtractive hybridisation (SSH), subtracting cell-suspension culture cDNAs from the embryoid cDNAs in order to obtain embryo-enhanced-transcripts that are differentially regulated during the transition of embryogenic competent callus to the mature embryogenic stage. A total number of 200 clones (suspension as tester) and 69 clones (embryoid as tester) from the forward and reverse subtraction cONA libraries, respectively, were randomly isolated and preliminary analysed by reverse Northern. Sequence analysis of 30 clones revealed that a large proportion of the genes, 57% were of unknown function while the remaining 43% were related to various biological pathways. Four SSH clones: 269-10-02 (ACC oxidase), 269-112-a2 (protein-disulphide isomerase like), 269-155 -A5 (6-phosphogluconolactonase-like) and 2524-4-b1 (no significant similarity) were selected for further characterisation. The transcripts of these clones were found to accumulate only in embryogenic tissues. Although their expression patterns signify a potential as an embryogenic marker, preliminary Northern analysis is insufficient to draw a clear conclusion about their role in embryogenesis.